Muscle and Its Diseases : An Outline Primer of Basic Science and Clinical Method - Siegel, Irwin M. (Chicago Year Book Medical Publishers, 1986)
This book attempts to provide the reader with a concise, problem-oriented outline of muscle basic sciences and neuromuscular diseases. The first of four sections, "Basic Science of Muscle," outlines in 46 pages anatomy, histology, growth and development, molecular basis of contraction, energetics, and biomechanics. "Clinical Techniques" is a brief review, in 58 pages, of the bedside examination and the various laboratory techniques employed in the workup of the weak patient: serum enzymes, electromyography, muscle biopsy, and genetics. "Classification and Diagnosis of Diseases" is a 64-page chapter outlining the clinical features of the major neuromuscular diseases, such as the spinal atrophies and dystrophies. "Management," constituting the last half of the book, describes the surgical and nonsurgical aspects of supportive care.
Include Index and Illustrations.
Keywords: Neuromuscular Diseases -- Muscular Diseases